The Role of Islamic Bank as Providers of Islamic Wealth Management in Enhancing the Potential of Waqf Funds - Ismail, Nurizal; Cahyo, Eko Nur (AL- IKTISAB Journal of Islamic Economic Law, 2017)
The purpose of this paper is to analyze the role of Islamic banks as providers ofIslamic wealth management product in relation with the enhancement of waqf funds.Theauthors use qualitative research that refers to the meanings, concepts, definitions,characteristics, metaphors, symbols and descriptions of the matter understudy by employscontent and descriptive analysis in order to get finding of the study. The data collectionis generated from Islamic sources: Qur’an, Sunnah and some Islamic literatures, andother sources such as books, journals, report documents, magazines and articles frominternet. These sources will be put in to coding and analyzed to answer the researchproblem of study. The role of Islamic wealth management is not only focusing on worldlyinvestment helping the clients’ need, but also hereafter investment. One of the instrumentsof wealth distribution that can be used for hereafter investment is waqf that helps theclients’ wealth to obtain blessing (barâkah) of Allah. By waqf, Islamic wealth managementinstrument can accomodate all models of waqf funds from cash waqf, insurance waqf,corporate waqf, etc. There are three options to of putting their wealth in waqf funds,they are: (i) family waqf, (ii) public waqf, and (iii) combination of waqf. All benefits ofthese waqf can contribute the the development of ummah. This paper is one of the veryfew conceptual studies concerning the practice of Islamic banking in implementing theproduct of wealth management for social purposes which is enhancement of waqf fundsfor the benefit of ummah.